Clinical application of an expanded reverse-island flap with two dorsal metacarpal arteries and dorsal metacarpal nerves in index- and middle-finger-degloving injury repair and amputation reconstruction. (February 2023) - Lin, Mei; Zuo, Xi; He, Fen; Fu, Qiuyuan; Li, Degui; Zuo, Zhongnan
Summary: The dorsal metacarpal artery flap (DMAF) is irrefutable as an effective way of repairing long finger defects, and hand surgeons might consider using it for long finger reconstruction or degloved injury repair. Unfortunately, the DMAF containing a single dorsal metacarpal artery (DMA) hinders the treatment effect. The sensory restoration of long fingers and the reconstruction of phalangeal joints and tendon grafts are unsolved challenges as well. We reported our experience in reconstructing the index and middle finger by a reverse-island flap with two DMAs and dorsal metacarpal nerves (DMNs) with blood supply. We reviewed ten patients with finger-crush injuries affecting eight index fingers and two middle fingers. Degloving injuries occurred in two patients, and finger amputations occurred in eight others. Two patients received simple flap reconstruction, and eight received finger reconstruction, including seven from abandoned phalangeal joints and tendon grafts of the severed finger and one from the iliac crest bone graft. All patients underwent finger reconstruction by an expanded reverse-island flap consisting of two DMAs and DMNs up to a maximal size of 9 × 8 cm 2 . Postoperative follow-up evaluation showed a satisfactory appearance and functional recovery of the reconstructed fingers. We posit that the expanded reverse-island flap involving two DMAs and DMNs constitutes a feasible and safe option for restoring a severely damaged index or middle finger, particularly for patients who are unwilling to undergo toe-to-finger transplantation to reconstruct the injured long fingers.